Developing and Delivering a Needs‐Based Integrated Pest Management Program for Public School Grounds Employees. Issue 1 (20th December 2016) - Kowalewski, Alec R.; Stock, Tim W.; McDonald, Brian W.; Mattox, Clint M.; Daviscourt, Brian L.
Abstract : Core Ideas: We developed an engaging and needs‐based IPM training curriculum for public school IPM and Coordinators and grounds employees in the Portland Metropolitan area. Although other training options are available, none specific to the needs of the Oregon school grounds employees were available prior to this pilot project. We used a focus group and survey to identify high‐priority training topics. We conducted site visits to confirm the severity of these issues and determine if other IPM‐related topics need to be incorporated into the future training events. Panel discussions and hands‐on field demonstrations were used to foster active and hands‐on education. Oregon Statute requires all Oregon schools to adopt an integrated pest management (IPM) plan, create a list of acceptable low‐impact pesticides, designate an IPM Coordinator, participate in annual training for IPM Coordinators, and provide periodic training for other school employees. To assist Oregon schools in meeting the requirements of the Oregon IPM in schools law, we developed an engaging and needs‐based IPM training curriculum for public school IPM Coordinators and grounds employees in the Portland Metropolitan area. We used a focus group and survey to identify high‐priority training topics. These topics were (1) landscape rodent management, (2) landscape and turf weed management, (3) hardscape weed management, (4) building a low‐maintenance landscape, and (5) maximizing low‐impact pesticides. We conducted site visits to confirm the severity of these issues and determine if other IPM‐related topics need to be incorporated into the future training events. Four separate training events were held in two different school districts. The four training events collectively reached 66 employees from 15 of the 23 school districts in the Portland area. On‐site surveys were used to assess the quality of the training; follow‐up focus group interviews and an on‐line survey were used to quantify the impacts of this training. According to the survey, the majority of the participants (67%) felt the training improved their knowledge of turf and landscape IPM. Final assessment determined that the majority of attendees have used the provided take home material (85.7%) and plan to decrease pesticide use by using the skills they learned (71.4%).